Běloruská národní idea na začátku 20. století - Smoliančuk, Alexandr (Lidé města, 2006)
Formation of the modern Byelorussian nation fits into a context of analogous processes of those Central European nations not having their own statehood, that entered the “period of nationalisms” (the end of 18th until the beginning of 20th century). In this case, national formation was accomplished through national movements seeking cultural and social emancipation. Disintegration of primordial multiethnic societies and disintegration of large states results in creation of ethnocultural nations which Miroslav Hroch calls “small European nations”.They were formed primarily as culturally centrist societies. Naturally, the “Byelorussian case” has its peculiarities. Heart of the matter is not that Byelorussians did not have their own statehood throughout almost the entire 20th century or that the term “national” does not describe the modern Byelorussian state, at all.